PROBLEMATIKA AKTA JAMINAN FIDUSIA (Suatu studi tentang Akta Jaminan Fidusia setelah berlakunya Sistem Pendaftaran Fidusia secara online ) - Suharto, R (Diponegoro Private Law Review, 2017)
Fiduciary Deed (AJF) must be authentic. An authentic deed should be made under the Article 1868 of the Civil Code, which one of the requirements must be made by or in the presence of a Notary. AJF regristration is one of the duties that must be performed, which can now be done online. There are several problems in AJF making and regristation. This legal writing is addressed to answer some of the problems exist. The problem studied is on how strength of evidence that the signing fiduciary deed is not done in the presence of Notary law relating to the protection of the parties and whether the certificate of fiduciary deed through online regristration can be legally valid. Key words : authenticity terms of a deedm fiduciary online registration.